Rapid evaluation method for uniformity of amorphous structure of polycarbonate injection molding product

Through p-FTIR and TMDSC technical means, the uniformity of PC injection molded products is directly evaluated from the perspective of microstructure, which solves the problem of difficulty in directly evaluating the uniformity of PC injection molded products in the prior art, and achieves effective guidance on product performance.

CN119846185APending Publication Date: 2025-04-18SICHUAN UNIV

Patent Information

Application Number
CN202311766313.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to directly evaluate the uniformity of PC injection molded products from the perspective of microstructure, which affects effective guidance on product performance.

Method used

Using p-FTIR and TMDSC, the molecular chain orientation degree and amorphous structure content were calculated respectively through polarization infrared spectroscopy and heat flow curve testing, and the amorphous structure uniformity of PC injection molded products was evaluated.

Benefits of technology

The direct, fast and accurate evaluation of the uniformity of amorphous structure of PC injection molded products has been achieved, and the understanding and guidance of product performance has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004619843890000041
    Figure BDA0004619843890000041
  • Figure HDA0004619843900000011
    Figure HDA0004619843900000011
  • Figure HDA0004619843900000012
    Figure HDA0004619843900000012
Patent Text Reader

Abstract

The invention provides a method for rapidly evaluating the uniformity of an amorphous structure of a polycarbonate (PC) injection molded product, which comprises the following steps of: obtaining the PC product through injection molding, representing polarized infrared spectrograms at different positions of the PC injection molded product by using a Fourier transform infrared spectrometer with a polarization mode, and calculating the uniformity of the amorphous structure of the PC injection molded product according to the absorbance of a PC characteristic peak at different polarized light angles. Calculating an infrared dichroism ratio and an amorphous molecular chain orientation degree; and the contents of rigid amorphous and movable amorphous in the PC injection molded product are represented by a differential scanning calorimeter with a temperature adjustment mode. The uniformity of the amorphous structure of the PC injection molding product is evaluated by comparing the difference of the orientation degrees of different positions of the PC injection molding product and combining the difference of the content of rigid amorphous and the content of movable amorphous. According to the method, the advantages and disadvantages of the injection molding products can be quickly evaluated, the high-performance polycarbonate injection molding products with uniform amorphous structures can be selected, and meanwhile, the method also has important guiding significance for guiding polycarbonate injection molding processing structure regulation and process setting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of characterization of amorphous polymer materials, and in particular relates to a method for quickly evaluating the uniformity of amorphous structures of PC injection-molded products. Background Art

[0002] PC, due to its advantages of light weight, high strength, good transparency, strong impact resistance, strong heat resistance and good dimensional stability, is widely used in important civil and military fields such as architectural glass, display devices, optical lenses, automotive transparent parts, electronic appliances, and aerospace aircraft windows. Injection molding is the most important molding method for preparing PC products. However, there are complex processing external fields (such as temperature field, pressure field, shear flow field, etc.) in injection molding, and these external fields are coupled with each other and unevenly distributed, resulting in uneven microstructure of PC products. As a non-crystalline polymer, the uniformity of its amorphous structure directly affects its important properties such as optics and mechanics. Therefore, it is of great significance to reasonably and efficiently evaluate the uniformity of the amorphous structure of PC injection molded products.

[0003] At present, the quality of PC products is usually evaluated by analyzing and testing the specific macroscopic properties of the products. For example, the size and distribution of internal stress, optical transparency, and mechanical properties of PC products can be compared. The above methods can indirectly reflect the uniformity of the internal structure of PC products to a certain extent. However, there is currently no method that can directly evaluate the uniformity of PC products from the perspective of microstructure. We know that processing determines structure, and structure determines performance. Clarifying the amorphous structure and distribution of PC products will help to guide the setting of PC injection molding process and microstructure regulation, thereby providing guidance for the "fixed structure" processing to prepare PC injection molding products with the required performance. Therefore, it is of great practical significance to develop a direct, fast, and efficient evaluation method based on PC amorphous structure. Summary of the invention

[0004] The purpose of the present invention is to provide a method for quickly evaluating the uniformity of the amorphous structure of PC injection molded products, so as to quickly evaluate the quality of PC injection molded products and select high-performance PC products with uniform amorphous structure. At the same time, it can also guide the structural control and process setting of PC injection molding processing to achieve "fixed structure" processing.

[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution.

[0006] A rapid evaluation method for the uniformity of amorphous structure of PC injection molded products comprises the following steps: 1) preparing PC injection molded products by injection molding; 2) performing p-FTIR characterization: determining 5 sites for analysis at equal distances from the near gate to the far gate on the PC injection molded products; installing a polarization accessory in an infrared light path, placing the site to be analyzed on the infrared light path, adjusting the angle of the polarizer every 10° from 0 to 180°, and collecting in a transmission mode to obtain infrared spectra of the sample at the analysis site at different polarization angles; selecting PC characteristic absorption peaks, obtaining absorbance at mutually perpendicular polarization angles (such as 0° and 90°), and calculating the molecular chain orientation by an infrared dichroic ratio formula; performing the same method on other selected sites of the PC injection molded products; 1) Carry out p-FTIR test on samples of the four determined analysis sites, and calculate the orientation degree; 2) Carry out TMDSC test: Use TMDSC to obtain the heat flow curve of PC injection molded products during the heating process, and obtain the relaxation heat capacity of the glass transition region through reversible heat flow and irreversible heat flow tests. Combined with the relaxation heat capacity of PC in a completely active amorphous state (fixed value), calculate the content of rigid amorphous and active amorphous; 3) Evaluate the structural uniformity of the product: Compare the differences in amorphous structure parameters (molecular chain orientation degree, rigid amorphous and active amorphous content) at different positions of the same product, and make a preliminary evaluation of the uniformity of the amorphous structure; and calculate the variance or standard deviation of the above amorphous structure parameters at the five sites to further evaluate the uniformity of the overall amorphous structure of PC injection molded products.

[0007] Furthermore, the wave number range of the characteristic absorption peak used for polarized infrared characterization is 1200-1350 cm -1 , further, the wave number is selected to be ~1230cm -1 The characteristic absorption peaks were characterized.

[0008] Furthermore, the initial materials for preparing PC injection molded products include pure PC and PC blends, and the blends may include any one of PC / ABS alloy, PC / ASA alloy, PC / PBT alloy, PC / PET alloy, PC / PET / elastomer blend, PC / MBS blend, PC / PTFE alloy, and PC / PA alloy.

[0009] Furthermore, the melt index of the initial material used to prepare the PC injection molded product is 2.0-30.0 (at 300° C., 1.2 kg) and the molecular weight is 200,000-100,000 g / mol.

[0010] Furthermore, the injection molding processing methods include ordinary injection molding, injection compression molding, vibration injection molding, etc.

[0011] Furthermore, the thickness of the PC injection molded product used for structural analysis is 0.1 to 2.0 mm.

[0012] Furthermore, during the injection molding process, the mold temperature is 25-100° C., the holding pressure is 50-100 MPa, and the injection rate is 50-200 mm / s.

[0013] Furthermore, PC injection molded products include dumbbell-shaped splines, rectangular splines, square sheets, and irregular complex products.

[0014] Beneficial technical effects of the present invention:

[0015] The present invention provides a rapid evaluation method for the uniformity of amorphous structure of polycarbonate injection molded products, which has the following advantages compared with the prior art:

[0016] (1) The present invention evaluates the uniformity of PC products from the perspective of microscopic amorphous structure, which is more direct than the current method of indirectly reflecting the uniformity of the internal structure of PC products through specific macroscopic properties of the products (such as the magnitude and distribution of stress, the degree of optical transparency, and the difference in mechanical properties, etc.);

[0017] (2) The present invention uses p-FTIR to characterize PC products, which can obtain quantitative information on the orientation of amorphous molecular chains. This characterization method is non-destructive and will not damage the sample. The PC products are characterized by TMDSC, which can obtain quantitative information on rigid amorphous and active amorphous. The amount of sample required for characterization is extremely small (3 to 8 mg).

[0018] (3) The evaluation method provided by the present invention is simple and easy to implement, and can clarify the amorphous structure and distribution of PC products in a short time, and can accurately and quickly characterize the uniformity of the amorphous structure of PC injection molded products, with high evaluation efficiency;

[0019] (4) The evaluation method provided by the present invention can in turn guide the PC injection molding process setting and microstructure regulation, thereby providing guidance for the "fixed structure" processing to prepare PC injection molded products with required performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0021] Figure 1 A schematic diagram of the positions of analysis points selected from the near gate to the far gate at equal distances on a dumbbell-shaped PC injection molding specimen for testing polarized infrared spectra;

[0022] Figure 2 This is the transmission infrared spectrum of the sample at position 3 of the PC injection molding strip at a polarization angle of 0 to 180°;

[0023] Figure 3This is the TMDSC curve of the sample at position 3 of the PC injection molding strip. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they are carried out according to the conditions recommended by the normal conditions or the manufacturers. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, it is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by those skilled in the art according to the above-mentioned invention content still belong to the scope of protection of the present invention.

[0025] Example

[0026] This embodiment provides a method for quickly evaluating the uniformity of amorphous structure of polycarbonate injection molded products, and the specific process is as follows:

[0027] (1) PC products made by injection molding

[0028] PC pellets with the brand 1250Y of Teijin Co., Ltd. of Japan were selected as raw materials. First, they were dried in a vacuum drying oven at 120°C for 8 hours to remove the moisture in the raw materials. Subsequently, the dried PC pellets were injection molded. A dumbbell-shaped mold core with a total length of 7.5 cm, a gauge length of 3 cm, a middle width of 0.5 cm, and a thickness of 0.5 mm was selected. The melt temperature was set to 295°C, the injection rate was 150 mm / s, the injection pressure was 75 MPa, the holding pressure was 60 MPa, the holding time was 4 s, and the mold temperature was 75°C to obtain a dumbbell-shaped PC injection molded product.

[0029] (2) Characterization of molecular chain orientation at different positions of PC injection molded strips using p-FTIR

[0030] On the prepared PC injection molding specimen, five points with equal distances from the near gate to the far gate were selected as the test sites ( Figure 1 ). Install the polarization accessory in the infrared light path, place the sample at the analysis position 3 of the PC injection molding specimen on the infrared light path, adjust the polarizer angle from 0 to 180° every 10°, and adjust the angle of the polarizer in the transmission mode from 0 to 4000cm -1 The infrared spectra of the sample at different polarization angles at the analysis site 3 were obtained by scanning within the wave number range ( Figure 2 ); Select PC between 1200 and 1350 cm -1 The characteristic absorption peaks in the wave number range (these peaks reflect the vibration of the PC polyester main chain) are obtained at mutually perpendicular polarization angles (such as 0° and 90°) (A ∥ and A⊥ ), the molecular chain orientation degree (f) is calculated by the infrared dichroism ratio (D), the formula is as follows:

[0031] D=A || / A ⊥ , f=(D-1) / (D+2)

[0032] The same method was used to perform p-FTIR tests on the other four selected analysis site samples of PC injection molded products, and the orientation degree was calculated. -1 The orientation results calculated from the characteristic peaks are shown in the following table:

[0033] Analysis site 1 2 3 4 5 Orientation degree f 1.12% 1.13% 1.04% 1.22% 0.87%

[0034] (3) Using TMDSC to characterize the content of rigid amorphous and active amorphous in different positions of PC injection molded strips

[0035] On the prepared PC injection molding specimen, five points with equal distances from the near gate to the far gate were selected as the test sites ( Figure 1 ), a small amount of PC sample was selected at each test site for TMDSC characterization. Analysis site 3 was selected, 5.56 mg of PC sample was cut with a blade, and placed in the sample crucible of DSC. The program was set to amplitude ±1.27°C, heating range 100-200°C, heating rate 4°C / min, and the heat capacity curve of the PC sample during the heating process was obtained ( Figure 3 ). Combining the reversible heat flow and irreversible heat flow of PC during the heating process, the T of PC was obtained by TRIOS software analysis. g The heat capacity step (ΔC p ), and the content of active amorphous (MAF) in which the molecular chain movement is not restricted and rigid amorphous (RAF) affected by the smectic conformation in PC are calculated by the following formula:

[0036]

[0037] Where ΔC p 0 is the standard melting step of PC with only active amorphous phase at the glass transition, ΔC p 0 =0.25J / (g·℃),X c X is the content or crystallinity of the crystalline part in the PC injection molded product. Since the PC obtained under this injection molding condition is usually an amorphous structure, X c is regarded as 0, so the content of rigid amorphous can be directly calculated by 1-X MAF Perform calculations.

[0038] The same method was used to perform TMDSC tests on the other four selected analysis site samples of PC injection molded products, and the contents of rigid amorphous and active amorphous at each location were calculated. The results are shown in the following table:

[0039] Analysis site 1 2 3 4 5 Active amorphous content 74.8% 71.2% 80.4% 73.2% 71.6% Rigid amorphous content 25.2% 28.8% 19.6% 26.8% 28.4%

[0040] (4) Evaluation of the uniformity of amorphous structure of PC injection molded products

[0041] By comparing the orientation results in step (2) of the above embodiment, it can be seen that the molecular chain orientations at different analysis sites of the PC injection molding strips are relatively low (≤1.22%) and the difference is not large. By comparing the rigid amorphous and active amorphous contents in step (3), it can be seen that there are certain differences in the amorphous phase structure at different analysis sites of the PC injection molding strips. In addition, in order to further evaluate the uniformity of the overall amorphous structure of the PC injection molding products, especially to compare the uniformity of the amorphous structure between different PC injection molding strips, the variance or standard deviation of the amorphous structure parameters (orientation, rigid amorphous content, active amorphous content) of the samples at the 5 analysis sites selected at the same position on each PC injection molding strip can be further calculated, and the variance or standard deviation can be compared.

[0042] In summary, the characterization method based on the amorphous structure of polycarbonate processed parts of the present invention is used to first prepare polycarbonate injection molded parts, with the aim of providing a method for evaluating the uniformity of the amorphous structure of polycarbonate products. This method is simple and easy to implement, and can scientifically evaluate the uniformity of the amorphous structure of polycarbonate plastic products in a short time.

[0043] The specific implementation methods described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only an embodiment of the present invention and is not intended to limit the scope of protection of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of this application.

Claims

1. A rapid evaluation method for the uniformity of amorphous structure of polycarbonate injection molded products, characterized in that: The following steps are involved: (1) Preparing polycarbonate (PC) injection molded products by injection molding; (2) The amorphous structure of PC injection molded products was characterized using Fourier transform infrared spectroscopy; (3) Characterize the amorphous structure of PC injection molded products using differential scanning calorimetry; (4) Evaluate the uniformity of the amorphous structure of PC injection molded products.

2. The method for evaluating the uniformity of amorphous structure of PC injection molded products according to claim 1, characterized in that: Characterization was performed using Fourier transform infrared spectroscopy (p-FTIR) in transmission mode with polarization mode and differential scanning calorimetry (TMDSC) in temperature modulation mode.

3. The evaluation method according to claims 1 to 2, characterized in that: The uniformity of the amorphous structure of PC injection molded products was evaluated by using the orientation degree of amorphous molecular chains, the content of rigid amorphous and mobile amorphous.

4. The evaluation method according to claims 1 to 3, characterized in that: The wave number range of the characteristic absorption peak used for polarized infrared characterization is 1200~1350cm -1 .

5. The evaluation method according to claims 1 to 4, characterized in that: The PC material includes pure PC and PC blends, and the blends may include any one of PC / ABS alloy, PC / ASA alloy, PC / PBT alloy, PC / PET alloy, PC / PET / elastomer blend, PC / MBS blend, PC / PTFE alloy, and PC / PA alloy.

6. The evaluation method according to claim 5, characterized in that: The PC material has a melt index of 2.0 to 30.0 (at 300° C., 1.2 kg) and a molecular weight of 200,000 to 100,000 g / mol.

7. The evaluation method according to claim 1, characterized in that: The injection molding processing methods in step (1) include ordinary injection molding, injection compression molding, vibration injection molding, etc.

8. The evaluation method according to claims 1 to 7, characterized in that: During the injection molding process, the mold temperature is 25-100°C, the holding pressure is 50-100 MPa, and the injection rate is 50-200 mm / s.

9. The evaluation method according to claims 1 to 8, characterized in that: PC injection molded products include dumbbell-shaped splines, rectangular splines, square sheets, and irregular and complex shaped products.

10. The evaluation method according to claims 1 to 9, characterized in that: The thickness of PC injection molded products is 0.1 to 2.0 mm.

Citation Information

Patent Citations

  • Evaluation method for uniformity of continuous-fiber-reinforced composite resin

    CN106872675A

  • Method and apparatus for evaluation of liquid-crystal orientation film

    JP1998153523A

  • Method of evaluating molecular orientation of resin molding

    JP2016017907A

Cited By

  • Injection molding method and injection molding device for vehicle-mounted electronic structural component

    CN120069677A